2018
DOI: 10.1002/cssc.201801059
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable High‐Performance Thermoplastics: Synthesis, Characterization, and Enzymatic Hydrolysis of Bisguaiacol‐Based Polyesters

Abstract: The utilization of wood-derived building blocks (xylochemicals) to replace fossil-based precursors is an attractive research subject of modern polymer science. Here, we demonstrate that bisguaiacol (BG), a lignin-derived bisphenol analogue, can be used to prepare biobased polyesters with remarkable thermal properties. BG was treated with different activated diacids to investigate the effect of co-monomer structures on the physical properties of the products. Namely, derivatives of adipic acid, succinic acid, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 64 publications
2
45
0
Order By: Relevance
“…28 Moreover, 5Gp could serve as a novel sustainable bisphenol for the synthesis of biobased polymers. 29 Furthermore, 5Gq , 5Gr , and 5Gs were isolated in good to moderate yields (81%, 53%, and 55% respectively). When secondary amines 4t , 4u , and 4v were used as coupling partner, the corresponding tertiary amines 5Gt , 5Gu , and 5Gv were obtained in good yield.…”
Section: Resultsmentioning
confidence: 93%
“…28 Moreover, 5Gp could serve as a novel sustainable bisphenol for the synthesis of biobased polymers. 29 Furthermore, 5Gq , 5Gr , and 5Gs were isolated in good to moderate yields (81%, 53%, and 55% respectively). When secondary amines 4t , 4u , and 4v were used as coupling partner, the corresponding tertiary amines 5Gt , 5Gu , and 5Gv were obtained in good yield.…”
Section: Resultsmentioning
confidence: 93%
“…34 Previous studies report that guaiacol was successfully reacted with formaldehyde 38,39 and involved in other polymers. 34,40 Yet, to the best of our knowledge, no study has reported the reaction with aromatic dialdehydes. Moreover, phenolic structures can be also provided from tannins 41 which are polyphenolic molecules found in all kinds of plant.…”
Section: Introductionmentioning
confidence: 99%
“…sugar, lignin, cinnamic acid, etc.). [22][23][24][25][26][27][28][29][30][31] Among these building blocks, furan-based ones have attracted the most attention. [32][33][34][35][36][37][38][39] Particularly, 2,5-furan-dicarboxylic acid (FDCA) has been conveniently produced from sugar resources and used to synthesize various polyesters.…”
Section: Introductionmentioning
confidence: 99%